The Impact of Poverty and Human Development Index on Inequality of Income Distribution of Regency/City in North Sumatra - Murbanto Sinaga; Rika Surianto Zalukhu (International Journal of Economics and Management Research, 2022)
This research aims to analyze the impact of poverty and the Human Development Index (HDI) on inequality of income distribution of regency/city in North Sumatra province. This research is quantitative descriptive. The research was conducted in 33 regencies/cities in North Sumatra province. The type of data used is secondary data. Data is accessed online on the website of Central Statistical Agency (BPS) for North Sumatra Province. The data used includes poverty rate data, HDI and Gini Ratio. Data analysis used multiple linear regression analysis. The results showed that poverty had a positive and significant impact on inequality of income distribution of regency/city in North Sumatra province. HDI also has a positive and significant impact on inequality of income distribution of regency/city in North Sumatra province. The results of the simultaneous test conclude that poverty and HDI simultaneously have a significant impact on inequality of income distribution of regency/city in North Sumatra province. This research implicates on preparation of poverty alleviation programs and equal of income distribution of regency/city in North Sumatra province.